PENGARUH PENGEMBANGAN KARIR DAN MOTVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL PENGENDALIAN PENDUDUK KELUARGA BERENCANA PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK (DINSOSDALDUKKBP3A) KABUPATEN PURBALINGGA - Janah, Siti; Supriatin, Dyah; Barima, Hima (Awatara Publisher, 2023)
This research is based on employee dissatisfaction to the management of DINSOSDALDUKKBP3A Purbalingga Regency one of information about varous carrier opportunities, so that employee are less motivated in planning or strategizing to get the position they want. This study aimed to determine the exent to which the influence of career development and work motivation affect employee performance of the Social Service Population Control Family Planning for Women’s and Child Protection (DINSOSDALDUKKBP3A) Purbalingga Regency. Type of research used quantitative approach with help of SPSS version 26.0. This study used multiple linier regression analysis. Primary data collection uses a questionnaire. The sampling technique uses purposive sampling that sampel used was 33 people with civil servant status (PNS). The result of this indicade that carrer development variable has positive and significant effect on employee performance with significant value of 0,00, work motivation has no effect on employee performance with a significant value of 0,757.